Penerapan Metode WASPAS Untuk Penentuan Penerima Beasiswa - Salahudin Robo; Siti Nurhayati; Muh. Riandi Widiyantoro; Maulana Ayub Ahmad (Journal of Information System Research (JOSH), 2023)
The need for funds or costs in education is important, one of those needs is scholarships, scholarships themselves are obtained based on several needs, one of which is that people can receive it if they are poor and there are difficulties in financing education. In that case, a system is needed that can help receiving scholarships. In that case, a decision support system for determining scholarship recipients was created using the Weighted Aggregated Sum Product Assessment method. The system used in this method is to provide several benchmarks as absolute values, after receiving a fixed value, the final result will be made in the form of a ranking arrangement of the data that has been made. The results of this study can assist in determining acceptance of the scholarship